A Brief Introduction to the Communicative Language Teaching - Xiaoqing, Liao. ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
The communicative language teaching approach is described, its theoretic history is reviewed, and classroom techniques are presented. The origins of the approach are found in research on the development of linguistic competence. Characteristics of the approach include: the goals of language use for communication; use of real-life communicative situations in classroom learning; emphasis on two-way communication; sufficient exposure to the target language; and development of all four language skills (listening, speaking, reading, writing). Links between linguistic and communicative competence are explored, and it is concluded that both are required, and must be taught, for effective communication. The roles of learner, teacher, methods, and materials in the communicative learning process are outlined. The teacher acts as manager of learning activities, advisor during activities, co-communicator, motivator, and evaluator. The student's role is primarily as communicator. Instructional materials serve to promote language use. Classroom procedures are both pre-communicative and communicative, and a combination of both conventional and communicative classroom techniques is advised. Four types of communicative activities (social formulas and dialogues, community-oriented tasks, problem-solving activities, role plays) are described and examples are offered. Contains 21 references. (MSE)
Microfiche.
Keywords: Classroom Communication; Classroom Techniques; Communicative Competence (Languages); Educational Strategies; Foreign Countries; Instructional Materials; Language Skills; Linguistic Theory; Second Language Instruction; Second Languages; Skill Development; Student Role; Teacher Role; Reports, Descriptive